The Distinction of Urban and Rural Education in Primary Schools - haerani, siti (Lembaga Bale Literasi, 2025)
This study aims to examine the education gap between urban and rural areas in Indonesia, especially at the primary school level. This difference is significant in various aspects, such as infrastructure availability, teacher quality, access to technology, and learning environment. Using a literature study method with a qualitative descriptive approach, this research collected data from various scientific journals and relevant books. The results show that schools in urban areas are generally more advanced with complete facilities and adequate teaching staff, while rural areas are still faced with infrastructure challenges, limited technology and a shortage of professional teachers. The findings emphasize the need for more inclusive and equitable policies in education development in order to create equitable access and quality of education for all the nation's children, both in cities and villages